New insights on the role of urea on the dissolution and thermally-induced gelation of cellulose in aqueous alkali - Alves, Luis (2018)
The gelation of cellulose in alkali solutions is quite relevant, but still a poorly understood process. Moreover, the role of certain additives, such as urea, is not consensual among the community. Therefore, in this work, an unusual set of characterization methods for cellulose solutions, such as cryo-transmission electronic microscopy (cryo-TEM), polarization transfer solid-state nuclear magnetic resonance (PTssNMR) and diffusion wave spectroscopy (DWS) were employed to study the role of urea on the dissolution and gelation processes of cellulose in aqueous alkali. Cryo-TEM reveals that the addition of urea generally reduces the presence of undissolved cellulose fibrils in solution. These results are consistent with PTssNMR data, which show the reduction and in some cases the absence of crystalline portions of cellulose in solution, suggesting a pronounced positive effect of the urea on the dissolution efficiency of cellulose. Both conventional mechanical macrorheology and microrheology (DWS) indicate a significant delay of gelation induced by urea, being absent until ca. 60 °C for a system containing 5 wt % cellulose, while a system without urea gels at a lower temperature. For higher cellulose concentrations, the samples containing urea form gels even at room temperature. It is argued that since urea facilitates cellulose dissolution, the high entanglement of the cellulose chains in solution (above the critical concentration, C*) results in a strong three-dimensional network.